Biosensor Cell-Fit-HD4D for correlation of single-cell fate and microscale energy deposition in complex ion beams - Julian Schlegel; Hans Liew; Katrin Rein; Oleh Dzyubachyk; Jürgen Debus; Amir Abdollahi; Martin Niklas (STAR Protocols, 2022)
Summary: We present a protocol for the biosensor Cell-Fit-HD4D. It enables long-term monitoring and correlation of single-cell fate with subcellular-deposited energy of ionizing radiation. Cell fate tracking using widefield time-lapse microscopy is uncoupled in time from confocal ion track imaging. Registration of both image acquisition steps allows precise ion track assignment to cells and correlation with cellular readouts.For complete details on the use and execution of this protocol, please refer to Niklas et al. (2022). : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.